Elas na TV : a participação das jornalistas nas emissoras de televisão de Uberlândia : uma perspectiva em três tempos - Souza, Eliane Moreira de. (2017)
The female participation in the work occurred in an asymmetric way, marked by struggles and achievements in the organizational environment. In Brazil, it underwent transformations, beginning in the 1960s and 1970s, caused by the period of industrialization and the second wave of the feminist movement. This research aimed to analyze the work conditions of women journalists in TV stations in Uberlândia-MG, as well as the changes experienced in this organizational environment, from the late 1970s to the present day, through the opinions and experiences of women journalists. journalists and journalism students. To that end, a theoretical review was carried out that addresses the historical perspective of the insertion of women in the labor market, through issues such as segregation and precariousness, femininity and masculinity, harassment, appearance, remuneration, barriers in the organizational environment, the context of media companies and the profession of journalist. From the methodological point of view, the research was anchored in the interpretative paradigm, based on the studies of the approach of socialist feminism, use of the case study method and qualitative approach. The data collection was done through 27 semi-structured interviews and 1 structured with journalists who work and worked in the journalism departments and 2 focus groups with Journalism students from 2 higher education institutions. Three different scripts were prepared for each group of respondents, all anchored in 3 dimensions identified from the theoretical-empirical referential: professional experience; organizational environment and professional growth. The interviews and focus groups were recorded, later transcribed and the data interpreted, through content analysis and identified 8 categories of analysis: competencies, areas of action (grouped in the professional experience dimension); gender, appearance, harassment, compensation (in the organizational environment dimension); barriers and empowerment (in the professional ascension dimension). As results, it was pointed out that, unlike the environments of the 1970s and 1980s, when the newsrooms were mostly male, today there is a balance between the number of men and women. If in the past they were deprived of certain subjects of news reports, today they go through all the subjects. The disparity in the salaries of men and women, when compared to the past, was smaller according to the results of this research. The conquest of the organizational space took place through attitudes based on initiative and persistence, characterizing the psychological empowerment or, through the training, identifying the educational empowerment. Regarding the appearance, if in the past, manuals defined the patterns of makeup and clothing, they have now been abolished, but collections still bother professionals and students. Harassment, especially by respondents, often occurs. Despite the advances and with the women occupying different positions, they are not in the positions of direction of journalism. In turn, students feel insecure to act in the market for the training they have received and most say they are disenchanted with the profession. In this way, the study points to changes in the last four decades, however, there are still remnants of an organizational environment that takes on the appearance, carries prejudices and machismo and demands more from the woman who can not reach the top of the organization.